Pengaruh Temperatur Pencampuran Terhadap Campuran Ac-Bc Yang Menggunakan Batu Gunung Kongkang Kesu’ - Iknasisus Saroan; Alpius; Eltrit Bima Fitrian (Paulus Civil Engineering Journal, 2023)
In pavement layers, temperature is very important in affecting the strength of the asphalt mixture. Therefore, if the asphalt mixture is not at a certain temperature, the bond between aggregates will decrease and the mixture will become weak. The aim and purpose of this study was to test the mixing temperature of his AC-BC mixture using 5% asphalt. The methodology of this paper is AC-BC blend composition design and Marshall immersion testing to obtain residual Marshall stability values. It can be seen from the results of the tests carried out that values ​​for AC-BC mixtures were obtained for each variation at the mixture temperatures used, i.e. 120°C, 130°C, 140°C, 150°C and 160°. . C Stabilized value 1677.06 to 1940.40 kg, flow rate 3.87 to 2.92 mm, VIM 4.76% to 3.35%, VMA 16.41% to 15.17%%, VFB 70.01% to 77.92% Mixture temperature is Marshall parameter.